Las algas rojas como fuente de compuestos bioactivos cosmecéuticos. - Vega Sánchez, Julia; Moreira, Bruna R.; Pereira, Débora T.; Bonomi-Barufi, José; López-Figueroa, Félix (My University, 2023)
Algae present a great molecular diversity with a wide range of bioactivities, among which antioxidant and photoprotective capacity highlighted for their potential cosmeceutical applications. Mycosporine-like amino acids and phenolic compounds present both properties and are synthetize under stress conditions like high UV radiation. These compounds can be use by the cosmetic industry as new active principles, which are natural, biodegradable and non-toxic.
Keywords: Rodofíceas; Cosméticos - Industria; Biotecnología farmacéutica; Algas; Porphyra; Fotoprotección; Cosmecéutica